Facial soft tissue changes and volumetric analysis of upper airways in patients undergoing surgically assisted rapid maxillary expansion using a transpalatal distractor - Carlos Augusto de Jesus Oliveira Gonçalves; João de Jesus Viana Pinheiro; Marcelo Newton Carneiro; Ana Karla da Silva Tabosa; Roberto Carlos Rivadeneira Cárdenas; José Thiers Carneiro, Jr (Brazilian Journal of Otorhinolaryngology, 2024)
Objective: To verify changes in facial soft tissue using the RadiANT-DICOM-viewer and Dolphin Imaging software, through linear measurements of tomographic points in a 3D reconstruction of the face and volumetric evaluation with three-dimensional measurements of the upper airways of patients with transverse maxillary discrepancy undergoing Surgically Assisted Rapid Maxillary Expansion (SARME). Methods: Retrospective, transverse, and descriptive study, through the analysis of computed tomography scans of the face of patients with transverse maxillary discrepancy, treated from July 2019 to December 2022. The sample consisted of 15 patients of both sexes, aged 21–42 years old, who underwent surgically assisted rapid maxillary expansion using the transpalatal distractor. Analysis was performed through linear, angular, and three-dimensional measurements in millimeters, in the preoperative and late four-month postoperative period, in frontal 3D tomographic images of the face, in the region of the width of the nose and alar base and also angular measurement in the lateral tomography for the angle nasolabial and upper airways of rhinopharynx, oropharynx and hypopharynx. Results: There was an increase in nasal width with an average of 1.3467 mm and an increase in the alar base with an average of 1.7333 mm. A significant difference was found in the pre- and postoperative assessments of the measurements of nasal width, alar base and nasolabial angle, as well as the upper airways in all their extension. The results favour a better understanding of the professional and the patient regarding the diagnosis and management of patients with transverse maxillary width discrepancies. Conclusion: Although our study shows an increase in soft tissues after SARME, no aesthetic changes are observed clinically, and all patients report significant respiratory improvement. SARME may therefore contribute to the improvement of professionals working in the field of oral and maxillofacial surgery and orthodontics. Level of evidence: Level 4.